The Differences In The Effectiveness of Benson Relaxation and Massage Efflurage On The Intensity of Back Pain With History of Low Back Pain In Adults - Ramayanti, Eva Dwi (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Low Back pain is a complaint of back pain due to the non-ergonomic position of activities. Complementary treatments are benson relaxation and eflurage massage. The purpose of this study was to determine the differences in the effectiveness of massage therapy and relaxants in reducing pain levels. Population in this study were people with a history of low back pain. It was 20 people.There are 2 treatment groups. Massage and relaxation grup. Data was collected using numerical pain scalers at the beginning and at the end of the treatment. Univariate data were analyzed with frequency distribution. Bivariat test were analyzed by Wilcoxon and man-whetnet test. There was an effect of giving benson relaxation an massage on the level of back. There is difference in the effectiveness of the two therapies on the level of pain. Efflurage massage is more effective in reducing pain.